Answer:
$7200 in the fund rose 6% n $2800 in the fund rose 9%
Step-by-step explanation:
let x be the amount in the fund rose 6%
gain in one year=x*6%=0.06x
total amount is 10000
so amount in the fund rose 9% = 10000-x
gain in one year=(10000-x)*9%=900-0.09x
total gain=0.06x+900-0.09x=900-0.03x
=684
900-684=0.03x
0.03x=216
x=7200
the other fund amount=10000-7200=2800
The answer is A
hope you found this usefull
Answer:
x=9
Step-by-step explanation:
Step 1: Simplify by both sides of the equation.
80-3x=53
80+-3x=53
-3x+80=53
Step 2: Subtract 80 from both sides.
-3x+80-80=53-80
-3x=-27
Step 3: Divide by both sides by 3.
-3x/-3 = -27/-3
x=9
above, -6 and -<span>1 2x2</span> - 6x - 1x - 3. Step-4 :